Association between the cytotoxic T-lymphocyte antigen-4 mutations and the susceptibility to systemic lupus erythematosus; Contribution markers of inflammation and oxidative stress - Tanhapour, M.; Vaisi-Raygani, A.; Bahrehmand, F.; Khazaei, M.; Kiani, A.; Rahimi, Z.; Nomani, H.; Tavilani, H.; Pourmotabbed, T. (Cellular and Molecular Biology, 2016)
The cytotoxic T lymphocyte antigen-4 (CTLA-4) also known as CD152 (cluster of differentiation 152) is a crucial negative regulator of the immune system. This protein receptor provides negative signals in order to suppress T-cell activation and immune attack against self-antigens, although its role is unclear.  The ability of CTLA-4 to limit T cell-mediated immune response has made it a major target in treatment of tumors and autoimmune diseases such as systemic lupus erythematosus (SLE). In this study, we investigated whether CTLA-4 G-1661A and CTLA-4 T-1722C mutations are associated with SLE. So one hundred nine SLE patients and 101 gender and age-matched unrelated healthy controls were recruited for this case-control study. The promoter mutations were detected by PCR-RFLP, neopterin, malondialdehyde (MDA) and serum lipid concentration were determined by HPLC and enzyme assay, respectively. Result: We found that both codominant (AA vs. GG) and recessive (AA vs. GA+GG) CTLA-4 G-1661A mutation significantly decreased the risk of SLE by 1.7 and 3.7 times, respectively.  Interestingly, SLE patients with AA genotypes of CTLA-4 G-1661A have lower neopterin and MDA concentration compared with GA+GG genotypes. The overall distribution of CTLA-4 T-1722C genotypes and alleles in SLE patients were similar to those in control group. In conclusion, our findings showed, that there is an association between systemic inflammatory markers, oxidative stress and the CTLA-4 G-1661A GG+AG genotypes, MDA and neopterin which are the most conventional risk factors for coronary heart disease, therefore these mutations may be consider as a risk factor for susceptibility to heart disease in SLE patients.